Künstliche Intelligenz in der deutschen Wirtschaft: OhneDigitalisierung und Daten geht nichts - Barbara Engels (Wirtschaftsdienst, 2023)
– Artificial Intelligence (AI) holds immense potential for enhancing prosperity. However, the adoption of AI in German businessesremains limited, with only 19 % of companies utilizing AI in 2022. The successful implementation of AI relies on two key prerequisites:a company's digitalisation and data economy readiness. The Digitalisation Index reveals slow progress in digitalisation across sectors,indicating a need for increased efforts. Additionally, companies must enhance their data economy readiness to efficiently utilize data forAI applications. Failing to tap into the potential of AI may result in significant competitive disadvantages in the future.
Keywords: O31; O33; Q55; 330; Unternehmen; Digitalisierung; Künstliche Intelligenz; Deutschland; Unternehmen; Digitalisierung; Künstliche Intelligenz; Deutschland